Reimagining Credit Underwriting with Agentic AI : Real-Time Decisions, Transparent Scoring, and Inclusive Automation - Sankara Reddy Thamma, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Agentic Artificial Intelligence (AI) is redefining how we approach credit underwriting—making it faster, fairer, and more transparent. In this paper, we present a modular agent-based architecture designed for real-time lending decisions that prioritize ethical reasoning and regulatory alignment. Our system increased approval rates for underserved borrowers by 35%, cut decision latency from 48 hours to under 3 minutes, and achieved a 92.3% AUC in default prediction. We walk through the full stack—from data pipelines and multi-agent design to case studies and evaluation metrics—and share practical strategies for governing AI in financial services responsibly.
Keywords: Agentic AI; Explainable AI; Fair Lending; Credit Scoring; Ethical Automation; Financial Inclusion; Regulatory Compliance